Communication and Language Use in the Multinational Company - Kočárová, Katarína (2016)
This Master Thesis aims to provide a clear overview about corporate communication practices and importance of a common corporate language in the multinational corporation with diversified portfolio of employees. Theoretical part introduces theoretical background which are further applied into practices in the practical part of the paper. This academic paper critically looks at a practices within a particular multinational corporation and its practical application which influences efficiency at the work place.